Talcum powder or aqueous gel to aid external cephalic version: a randomised controlled trial - Vallikkannu, N.; Nadzratulaiman, W.N.; Omar, S.Z.; Lay, K.S.; Tan, P.C. (BioMed Central, 2014)
Background: External cephalic version (ECV) is offered to reduce the number of Caesarean delivery indicated by breech presentation which occurs in 3-4 of term pregnancies. ECV is commonly performed aided by the application of aqueous gel or talcum powder to the maternal abdomen. We sought to compare gel with powder during ECV on achieving successful version and increasing tolerability. Method: We enrolled 95 women (>= 36 weeks gestation) on their attendance for planned ECV. All participants received terbutaline tocolysis. Regional anaesthesia was not used. ECV was performed in the standard fashion after the application of the allocated aid. If the first round (maximum of 2 attempts) of ECV failed, crossover to the opposing aid was permitted. Results: 48 women were randomised to powder and 47 to gel. Self-reported procedure related median interquartile range pain scores (using a 10-point visual numerical rating scale VNRS; low score more pain) were 6 5-9 vs. 8 7-9 P = 0.03 in favor of gel. ECV was successful in 21/48 (43.8%) vs. 26/47 (55.3%) RR 0.6 95% CI 0.3-1.4 P = 0.3 for powder and gel arms respectively. Crossover to the opposing aid and a second round of ECV was performed in 13/27 (48.1%) following initial failure with powder and 4/21 (19%) after failure with gel (RR 3.9 95% CI 1.0-15 P = 0.07). ECV success rate was 5/13 (38.5%) vs. 1/4 (25%) P = 0.99 after crossover use of gel or powder respectively. Operators reported higher satisfaction score with the use of gel (high score, greater satisfaction) VNRS scores 6 4.25-8 vs 8 7-9 P = 0.01. Conclusion: Women find gel use to be associated with less pain. The ECV success rate is not significantly different.